SELF EFFICACYAND SOCIAL SUPPORT TO IMPROVE THE PSYCHOLOGICAL WELL BEING OF RAUDHATUL ATHFAL (RA) TEACHERS - Rusmiati; Hasanuddin; Risydah Fadilah (RADJA PUBLIKA, 2025)
Teachers are one of the factors that greatly influence the teaching and learning process to produce quality and highly competitive human beings. Teachers in carrying out their profession or work will certainly experience emotional challenges and require good psychological well being. This study aims to determine the role of self-efficacy and social support to improve the psychological well being of Raudhatul Athfal (RA) teachers. The subjects of the study were 266 honorary RA teachers in Langkat Regency. Measurements used a scale of psychological well being, self-efficacy and social support. Multiple regression analysis showed that there was a significant positive effect between self-efficacy and psychological well being (tx1y = 10,745 with p = 0.000 meaning p <0.05) and provided an effective contribution of 50.71%. Social support has a significant positive effect on psychological well being (tx2y = 2,176 with p = 0.030, meaning p <0.05) and provided an effective contribution of 8.64%. For the interaction effect, a significant influence of Self-efficacy and Social Support was obtained simultaneously on Psychological Well Being where the coefficient F = 192.334; with p = 0.000 means p <0.050. The effective contribution of both variables of self-efficacy and social support was 59.4% (R2 = 0.594). Thus, this study shows that self-efficacy and social support play a significant role in the psychological well being of RA teachers, both simultaneously and separately.